The Role of the Matahari Women's Group in Forest Area Management through the Village Forest Scheme in the Social Forestry Program in Sekabuk Village, Sadaniang District, Mempawah Regency - Dwiyana, Ersa; Chainar, Chainar; Sikwan, Agus; Purnama, Desca Thea; Marini, Marini (Journal of Business Management and Economic Development, 2024)
This study aims to determine the role of Sekabuk Village women's involvement in managing forest areas through the Social Forestry Program (PS). The method used in this study is a qualitative research method with a descriptive approach. The data source in the study was obtained through semi-structural, in-depth interviews with 7 key informants, which were determined through purposive sampling techniques. The writing of this thesis aims to provide an understanding of the implementation of social forestry programs involving the role of women in Sekabuk Village. The problem of the lack of involvement of women in resource management around the area that occurs in Sekabuk Village is quite interesting to study, considering that most of the Sekabuk Village area is a forest area. Based on the research conducted, the participation of women in Sekabuk Village was obtained through granting forest management rights by issuing group decrees, increasing women's capacity by providing training, developing forest-based economic businesses for women's groups, providing women's empowerment in forest area management, and conducting supervision and evaluation. So, the role of Sekabuk Village women in playing an active role in forest area management was revealed.